2017
DOI: 10.5530/ijper.51.3s.57
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Bryonia multiflora Extract on Pancreatic Beta Cells, Liver and Kidney of Streptozotocin-Induced Diabetic Rats: Histopathological and Immunohistochemical Investigations

Abstract: Objective: In this study, the ameliorative potential and antioxidant capacity of treated with different doses of Bryonia multiflora extract (BE) was investigated using histopathological and immunohistochemical changes in pancreatic beta cells, liver and kidney tissues of streptozotocin (STZ)-induced diabetic rats. Material and Methods: A total of forty-two healthy adult Wistar albino male rats were divided randomly into six groups as Control (C); Diabetes mellitus (DM); DM+Akarboz 20 mg/kg; DM+100 mg/kg BE ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…These accord with previous studies. 23,24 However, treatment with the P. stratiotes extract for 3 weeks was able to amelioratethese alterations to near normal status. This implies the potential of P. stratiotes extract to ameliorate hepatic and renal diabetes-associated complications.…”
Section: Resultsmentioning
confidence: 95%
“…These accord with previous studies. 23,24 However, treatment with the P. stratiotes extract for 3 weeks was able to amelioratethese alterations to near normal status. This implies the potential of P. stratiotes extract to ameliorate hepatic and renal diabetes-associated complications.…”
Section: Resultsmentioning
confidence: 95%
“…Intraperitoneal injection of the animals with STZ was done to induce diabetes (Uyar et al, 2017). Blood glucose level was measured after 72 hours by using glucometer after 1, 2, 3, and 4 week's intervals.…”
Section: Induction Of Diabetesmentioning
confidence: 99%
“…In addition to hepatic GSH reduction as result of increased ROS production and free radical scavenging activity inhibition agreed with Abd El-Fattah et al (2018) and Ahmed et al (2015), as well as other hepatic metabolic disturbances reduction in albumin and total protein, GGT serum elevation, AST and ALT, and ALP elevation after STZ induction was in accordance with histopathological findings and indicator of liver damage and thus otherwise alterations in the hepatic functions (Ahmed et al, 2015). Wang et al (2016) suggested that both oral anti-diabetic drugs and insulin may lead to insulin resistance besides many [E] Showing nearly normal histological structure in group-treated glibenclamide.…”
Section: Histopathological Assaymentioning
confidence: 99%
See 2 more Smart Citations